FRAX-based intervention thresholds for men in the Russian Federation: Expert consensus of the Russian association on osteoporosis - E. N. Gladkova; O. A. Nikitinskaya; I. A. Skripnikova; M. A. Myagkova; I. A. Baranova; Zh. E. Belaya; K. Yu. Belova; L. P. Evstigneeva; O. B. Ershova; B. V. Zavodovskii; O. V. Kosmatova; E. N. Otteva; et al. (Научно-практическая ревматология)
According to the European guidelines for osteoporosis, the same FRAX intervention threshold is suggested for men as for women. At the same time, in the Russian Federation, according to research data, an extremely low proportion of identified men who are subject to the initiation of osteoporosis therapy. The female intervention threshold identifies only 1.1 to 4% of men for treatment. Aim – to develop and evaluate various options for the intervention threshold using the FRAX calculator for men in the Russian Federation and adopt the most acceptable intervention threshold by consensus. Material and methods. Delphi voting was conducted among 18 Russian experts who have publications and personal reports about their experience with the FRAX calculator. For discussion, 5 intervention threshold options with the corresponding rationale based on the literature reference were presented, as well as the proportion of men of different ages to be initiated in each of the options (based on several Russian population-based studies). Anonymous voting was carried out using the Delphi method with questionnaire placed in the Google form. It was proposed to evaluate all options for intervention thresholds on a 9-point Likert scale. Consensus was considered reached if the intervention threshold reached a Likert score of 7 or more points in 80% or more of the experts. The rating of each intervention threshold option was expressed as mean and standard deviations. Results. In the first round of voting, the maximum rating and percentage of agreement is reached for the 9% fixed interference threshold option based on the FRAX calculation. The rating was 7.72±1.6 points, the percentage of experts’ agreement was 88.9%. A fixed threshold of 9% determined 13–19.5% of men aged 50 years and older to be treated for osteoporosis, while their proportion increased to 26–38% at the age of 85 years and older. Conclusion. The consensus of experts of the Russian association on osteoporosis suggests initiating treatment of osteoporosis in Russian men with a 10-year probability of major osteoporotic fractures according to FRAX of 9% or higher.